The role of autonomy and social support in the relation between psychosocial safety climate and stress in health care workers - Bo M. Havermans; Cécile R. L. Boot; Irene L. D. Houtman; Evelien P. M. Brouwers; Johannes R. Anema; Allard J. van der Beek (BMC, 2017)
Abstract Background Health care workers are exposed to psychosocial work factors. Autonomy and social support are psychosocial work factors that are related to stress, and are argued to largely result from the psychosocial safety climate within organisations. This study aimed to assess to what extent the relation between psychosocial safety climate and stress in health care workers can be explained by autonomy and social support. Methods In a cross-sectional study, psychosocial safety climate, stress, autonomy, co-worker support, and supervisor support were assessed using questionnaires, in a sample of health care workers (N = 277). Linear mixed models analyses were performed to assess to what extent social support and autonomy explained the relation between psychosocial safety climate and stress. Results A lower psychosocial safety climate score was associated with significantly higher stress (B = −0.21, 95% CI = −0.27 - -0.14). Neither co-worker support, supervisor support, nor autonomy explained the relation between psychosocial safety climate and stress. Taken together, autonomy and both social support measures diminished the relation between psychosocial safety climate and stress by 12% (full model: B = −0.18, 95% CI = −0.25 - -0.11). Conclusions Autonomy and social support together seemed to bring about a small decrease in the relation between psychosocial safety climate and stress in health care workers. Future research should discern whether other psychosocial work factors explain a larger portion of this relation. Trial registration This study was registered in the Netherlands National Trial Register, trial code: NTR5527 .